1996
DOI: 10.1007/bf02367137
|View full text |Cite
|
Sign up to set email alerts
|

Parasite communities of four fish species in the Wadden Sea and the role of fish discarded by the shrimp fisheries in parasite transmission

Abstract: Parasites were observed in medium-and small-sized fish taken from the discards of a commercial shrimper during seven different cruises in the tidal channels of the North Frisian Wadden Sea (S~deraue, North Sea) from April to September 1991. In total, 442 fish comprising four species (Sprattus sprattus, Hyperoplus lanceolatus, Ammodytes tobianus, Pomatoschistus minutus)were investigated. The parasite fauna consisted of 22 species. The parasite community structure of the 4 hosts was compared. The diet of the hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
1
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 36 publications
(43 reference statements)
4
23
1
1
Order By: Relevance
“…Our results as well as previous studies (Groenewold et al, 1996;Zander, 2005) show that parasitism is common in the analyzed four small fish species of the Wadden Sea. In total, we detected 16 different macroparasite species from six different phyla.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results as well as previous studies (Groenewold et al, 1996;Zander, 2005) show that parasitism is common in the analyzed four small fish species of the Wadden Sea. In total, we detected 16 different macroparasite species from six different phyla.…”
Section: Discussionsupporting
confidence: 91%
“…The diversity of the parasite communities from Atlantic herring, European sprat and lesser sand eel ranged from five to seven different parasite species and showed diversity indices in the range from 1.46 to 1.67, which is considerably higher than previously reported diversities from the German Wadden Sea of 0.95 for European sprat and 0.20 for lesser sand eel (Groenewold et al, 1996). In the past, many parasitological studies were exclusively based on morphological identification, but particularly nematodes or larval stages of parasites are difficult to identify at the species-level (Bhadury and Austen, 2010;Locke et al, 2010).…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…The very host specific is species of Capillaria, most oxyurids, and the philometrids Nilonema gymnarchi and Thwaitia bagri [3,5]. Globally, there is paucity of the literature on the helminth parasites of marine and estuarine fishes, with the following records available [6][7][8][9][10][11][12][13][14][15]. The neglect of marine fish parasitology has been attributed to ignorance of the occurrence, distribution, and taxonomy of the parasites in fish [13].…”
Section: Introductionmentioning
confidence: 99%
“…In the Baltic Sea, off the Polish coast, Markowski (1935) found 1-2 specimens in 8 of 520 examined specimens of the sand goby Pomatoschistus minutus (Pallas) and Groenewold et al (1996) found one adult D. minutus among 194 specimens of P. minutus from the southeastern North Sea. In the Øresund it was found in Pomatoschistus microps only, a brackish goby mostly living at depth less than 10 m. It is replaced by P. minutus at deeper waters.…”
Section: Discussionmentioning
confidence: 99%